Anaerobic digestion of recycled paper crumb and effects of digestate on concrete performance. (May 2023) - Hurst, George; Ahmed, Ash; Taylor, Steven; Tedesco, Silvia
Abstract: Paper crumb (PC) is a type of paper sludge residue from the wastepaper recycling industry. It is a by-product from the various fiber purification stages that is particularly composed of short cellulose fibers, lignin, organic compounds and inorganic filler residues. Despite representing a reject material for the paper recycling sector, this feedstock can be turned into a bioresource to enable cross-sector industrial symbiosis in the form of a more sustainable concrete, hence an opportunity for novel Net Zero supply chains. This study sought to valorise the PC by the sequential anaerobic digestion to produce methane (CH4 ) from the organic compounds, followed by utilization of the digestate as a water replacement in concrete. The 21-day digestion of PC yielded 163 ml CH4 per gram volatile solids and the resulting digestate improved concrete compressive strength up to 50% water replacement grade, meeting the requirements for structural grade (C32/40) applications with substitution grades up to 50% and 25%, with and without the addition of plasticiser respectively. In a minor capacity, the digestate reduced workability of the concrete mix, however we demonstrate this issue can be resolved by the addition of plasticiser or increased water to cement ratios. The admixture addition is important to facilitate pumpability on site and ensure satisfactory compaction. This study highlights the potential of anaerobic digestate as a concrete supplement (additive), which would improve the sustainability of both the construction and the paper sector. Graphical abstract: Image 1